2015
DOI: 10.1017/s0007114514003250
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition attributes and health effects of pistachio nuts

Abstract: Epidemiological and/or clinical trials have suggested that nut consumption has a beneficial impact on health outcomes such as hypertension, diabetes, CVD, cancer, other inflammatory conditions and total mortality. Nuts are nutrient-dense foods with a healthy fatty acid profile, as well as provide other bioactive compounds with recognised health benefits. Among nuts, pistachios have a lower fat and energy content and the highest levels of K, g-tocopherol, vitamin K, phytosterols, xanthophyll carotenoids, certai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 97 publications
(146 reference statements)
1
69
0
3
Order By: Relevance
“…Therefore, nutrients in pistachios can help individuals with pre-diabetes in reducing blood sugar and insulin. Moreover, research showed that consumption of pistachios had a positive effect on patients with diabetes (3,11,27). Diabetes is a disease characterized mainly by hyperglycemia, and carbohydrate, fat, and protein dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, nutrients in pistachios can help individuals with pre-diabetes in reducing blood sugar and insulin. Moreover, research showed that consumption of pistachios had a positive effect on patients with diabetes (3,11,27). Diabetes is a disease characterized mainly by hyperglycemia, and carbohydrate, fat, and protein dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Primary prevention of these phenomena with a healthy diet containing nuts, such as walnuts (1), almonds (2), and pistachios (3), is possible. Research has shown that almonds have high unsaturated fats and affect the blood lipids (decrease triglycerides, total cholesterol, and LDL), and guarantees the health of women and men (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antepfıstığı oksidatif stresin kontrolü ve kronik hastalık riskini azaltması üzerine önemli bir etkiye sahip olan yağda çözünen antioksidanların zengin bir kaynağıdır [33]. Antepfıstığı içerisinde bulunan E vitamininin antioksidan özelliği sayesinde Alzheimer hastalığının seyrini yavaşlattığı, bağışıklık sistemini güçlendirdiği, hücre bakımı ve yenilenmesine katkıda bulunduğu, koroner kalp hastalığı ve kanserin önlenmesinde etkili olduğu rapor edilmiştir [100].…”
Section: İnsan Sağliği Açisindan Antepfistiğinin öNemi̇unclassified
“…Kerman Province provides 67% of total Iranian pistachio, of which 70% belong to the Ohadi cultivar as the most important commercial cultivar in this region . The pistachio nut is a good source of nutrients, containing lipids, proteins, carbohydrates, dietary fibers, vitamins, minerals and phenolic compounds …”
Section: Introductionmentioning
confidence: 99%